Boosters for Carbon Neutrality: A 360° Approach - Salil Seth, Mrinal Kanti Mahato, Parveen Yadav, Mohd Irfan Pathan, Lokesh Tomar, (European Economic Letters (EEL), 2024)
Carbon information highlights the lacunae wherein eco-centric interventions are falling weak. In the present scenario of datafication, digitization & networking, it is imperative to resort to carbon-neutral pathways that may propel the society towards sustainability. Since, the attainment of carbon neutrality as per the objectives of G20 is a collaborative effort of both social sciences and sciences, a 360-degree approach for identifying the boosters of carbon neutrality is essential. These boosters may synergistically mechanize the achievement of carbon neutrality. This paper aims at drafting a conceptual frame that deciphers the boosting mechanism that may help in the attainment of carbon neutrality. Because of the novelty of the topic, this conceptual paper resorts to an exploratory research design with impetus on mixed qualitative approach engaging conceptual framework analysis & grounded theory. Based on the conceptual homogeneity of the sub-topics found relevant to the central theme, the literature was segregated into five conceptual frames for drawing inductive inferences. The deductions of the paper are anticipated to be a trailblazer for social advocates of carbon neutrality, green marketers, environmental strategists, academic cohort and even the statutory public bodies struggling to strike the chord of ‘net zero’ carbon emissions.